Naming of educational organizations as a marketing tool - Tepla, Oksana (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional Development, 2021)
This research focuses on building the brand of an educational institution. An important attribute of the brand is the name. The purpose of the article is to analyze and evaluate the methods of creating the names of private secondary schools, to identify the frequency of their use. The material base of the research is a card index of names of private educational institutions of the middle level, formed by the author in the process of research by a continuous sample of names. A total of 194 names were analyzed and systematized. The stages of creation of a name of an educational institution are considered. The requirements for a successful name of an educational institution are characterized. It is established that in Ukrainian education, naming has not yet become a common marketing tool. Only private educational institutions have mastered the methods and principles of naming, given the market of educational services and the possibility of its segmentation. The study describes 9 preferred methods of creating the names of secondary schools, including private schools. The most common are the associative method, based on the construction of certain positive connotations associated with the name of the institution, and the reference method. Nominal, appellate and conceptual methods, names of flora, fauna, natural phenomena are also often used. The results of the study show that the modern names of educational institutions are dominated by names of the pragmatic type. Whereas, the small number of non-pragmatic non-informative nominations is due to the fact that in conditions of high competition, names with a value that is not supported by an indication of the type of activity of the institution will not be remembered by the consumer. Prospects for further research of the names of educational institutions in terms of communicative-functional approach are proposed.